Using Concept Mapping to Improve the Writing Ability of the Eight Graders - Kalsum Maloho (Universitas Hamzanwadi, 2017)
This study - which is classroom action research in nature - was intended to develop concept mapping strategy to improve the writing ability of the eighth grade students. The subjects of this study were twenty students (Class VIII-B) of MTs PKP Manado, North Sulawesi in the academic year 2015-2016. This study was conducted in two cycles through some procedures: planning the action, implementing the action, observing the implementation, and reflecting the action. The data of the study were gathered using portfolio, observation checklist and field notes. The findings of the study indicated that concept mapping was successful in improving the students’ writing ability. The improvement could be seen from the increase of the students’ mean scores and the students’ involvement in writing activities. The mean scores obtained by the students in the two cycles were shown by the results of portfolios. While the students’ involvement in writing activities in the two cycles were shown by the observations checklists and field notes. From the findings, it can be inferred that concept mapping is not only effective in improving the writing ability of the students but also in enhancing their involvement in writing activities, particularly in generating and organizing their ideas.